A sensorless approach for tracking control problem of tubular linear synchronous motor - Nguyen Hong Quang; Nguyen Phung Quang; Nguyen Van Lanh (Institute of Advanced Engineering and Science, 2022)
As well-known, linear motors are widely applied to various industrial applicationsdue to their abilities in providing directly straight movement without auxiliary mechanical transmissions. This paper addresses the sensorless control problem of tubular linear synchronous motors, which belong to a family of permanent magnet linear motor. To be specific, a novel velocity observer is proposed to deal with an unmeasurable velocity problem, and asymptotic convergence of the observer error is ensured. Unlike other studies on sensorless control methods for linear motors, our proposed observer is designed by regrading unknown disturbance load in the tracking control problem whereas considering theoretical demonstrations. By adjusting controller parameters properly, the position and velocity tracking error converge in arbitrary small values. Finally, the effectiveness of the proposed method is verified in two illustrative examples.